Aquilaria species as potential anti-inflammatory agentsa review on in vitro and in vivo studies - Eissa, Manar A. (Tanjong Malim, 2020)
Aquilaria species as potential anti-inflammatory agentsa review on in vitro and in vivo studies by Eissa, Manar A.